A magnetic resonance imaging-based approach to quantify radiation-induced normal tissue injuries applied to trismus in head and neck cancer - Maria Thor; Neelam Tyagi; Vaios Hatzoglou; Aditya Apte; Ziad Saleh; Nadeem Riaz; Nancy Y. Lee; Joseph O. Deasy (Physics and Imaging in Radiation Oncology, 2017)
Background and purpose: In this study we investigated the ability of textures from T1-weighted MRI scans post-contrast (T1wpost) to identify the critical muscle(s) for radiation-induced trismus. Materials and methods: The study included ten cases (Trismus: ≥Grade 1), and ten age-sex-tumor-location-and-stage-matched controls treated with intensity-modulated radiotherapy to 70 Gy@2.12 Gy in 2005–2009. Trismus status and T1wPost were conducted within one year post-radiotherapy. For the masseter, lateral and medial pterygoids, and temporalis (M/LP/MP/T), 24 textures were extracted (Grey Level Co-Occurrence (GLCM), Histogram, and Shape). Univariate logistic regression with Bootstrapping (1000 populations) was applied to compare the muscle mean dose (Dmean) and textures between cases and controls (ipsilateral muscles); candidate predictors were suggested by an average p ≤ 0.20 across all Bootstrap populations. Results: Dmean to M/LP/MP (p = 0.03/0.14/0.09), one MP/T (p = 0.12/0.17), and three M (p = 0.14–0.19) textures were candidate predictors. Three of these textures were GLCM- and two Histogram textures with the former being generally higher and the latter lower for cases compared to controls. The Dmean to M and MP, and Haralick Correlation (GLCM) of MP presented with the best discriminative ability (area under the receiver-operating characteristic curve: 0.85, 0.77, and 0.78), and the correlation between Dmean and this texture was weak (Spearman’s rank correlation coefficient: 0.26–0.27). Conclusions: Our exploratory study points towards an interplay between the dose to the masseter, and the medial pterygoid together with the local relationship between the mean MRI intensity relative to its variance of the medial pterygoid for radiation-induced trismus. This opens up for exploration of this interplay within the radiation-induced trismus etiology in the larger multi-institutional setting. Keywords: Head and neck cancer, Radiotherapy, Trismus, Quantitative image, Texture, Radiomics